Telehealth utilization barriers among Alabama parents of pediatric patients during COVID-19 outbreak - Md Jillur Rahim; Pallavi Ghosh; Anne E. Brisendine; Nianlan Yang; Ryan Roddy; Mia J. Broughton; Alexis Kinzer; Martha Slay Wingate; Bisakha Sen (BMC, 2023)
Abstract Background Telehealth can improve access to evidence-based care at a lower cost for patients, especially those living in underserved and remote areas. The barriers to the widespread adoption of telehealth have been well documented in the literature. However, the barriers may not be the same for pediatric patients, who must rely on their parents or guardians to make healthcare decisions. This paper presents some of the leading barriers parents or guardians of pediatric patients report in using telehealth to meet their children's healthcare needs. Methods This cross-sectional survey was conducted in a tertiary care pediatric Emergency Department (ED) at a children's hospital in Alabama between September 2020 to December 2020. The parents or guardians of pediatric patients were asked about their reasons for not using telehealth despite having healthcare needs for their children, whether they canceled or rescheduled healthcare provider visits and facility visits, and whether the child's health conditions changed over the past three months. Descriptive analyses were conducted that explored the distribution of telehealth use across the variables listed above. Results Five hundred ninety-seven parents or guardians of pediatric patients participated in the survey, and 578 answered the question of whether they used telehealth or not over the past three months. Of them, 33.1% used telehealth, 54.3% did not, and 12.6% did not have healthcare needs for their child. The leading reason for not using telehealth was that the doctor or health provider did not give them a telehealth option, the second main reason was that they did not know what telehealth is, and the third leading reason was that the parents did not think telehealth would help meet healthcare needs for their child. Conclusions This study highlights the telehealth utilization barriers among underserved pediatric populations, including the need for physicians to proactively offer telehealth options to parents or guardians of pediatric patients. Improving health literacy is of paramount importance, given that a substantial proportion of parents were not familiar with telehealth. Policymakers and healthcare organizations should raise awareness about the benefits of telehealth which can improve healthcare access for underserved pediatric patients.